Pharmacokinetics of Favipiravir in Critically Ill Patients With COVID‐19 - Kei Irie; Atsushi Nakagawa; Hirotoshi Fujita; Ryo Tamura; Masaaki Eto; Hiroaki Ikesue; Nobuyuki Muroi; Keisuke Tomii; Tohru Hashida (Wiley, 2020)
Since December 2019, a novel coronavirus (severe acute respiratory syndrome‐coronavirus 2 (SARS‐CoV‐2)) infection has been rapidly spreading worldwide and causing the respiratory illness, coronavirus disease 2019 (COVID‐19). The antiretroviral drug favipiravir (FPV) has been experimentally used for COVID‐19 treatment since March 2020 in Japan. However, the pharmacokinetics of FPV in critically ill patients is unknown. We measured the serum concentration of FPV using high‐performance liquid chromatography in patients with severe COVID‐19 who were admitted to the intensive care unit and placed on mechanical ventilation. The patients were administered 1,600 mg of FPV twice daily on day 1, followed by 600 mg twice daily from day 2 to day 5 (or more if needed). Suspensions of FPV tablets were administered through a nasogastric tube. Seven patients were enrolled in this study. Forty‐nine blood samples were obtained from the eligible patients to evaluate FPV concentration. The FPV trough (after 8-12 hours) concentrations of most samples were lower than the lower limit of quantification (1 µg/mL) and half‐maximal effective concentration (9.7 µg/mL) against SARS‐CoV‐2 previously tested in vitro. FPV trough concentration in critically ill patients was much lower than that of healthy subjects in a previous clinical trial, which is a cause for great concern. Further study is required to determine the optimal strategy for treatment of patients with severe COVID‐19.